PENERAPAN PEMBERIAN AROMATERAPI LAVENDER UNTUK MENGATASI GANGGUAN POLA TIDUR PADA LANSIA HIPERTENSI PUSKESMAS SEI LANGKAI KOTA BATAM - Poetri Nadia; Yulia Devi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Sleep pattern disturbances are a common issue among the elderly with hypertension, significantly affecting their quality of life. This study aims to identify the effectiveness of lavender aromatherapy in managing sleep pattern disturbances in Mrs. T, an elderly patient with hypertension. A case study approach was used, involving assessment, diagnosis, intervention, implementation, and evaluation over three days. The assessment revealed that Mrs. T experienced sleep difficulties accompanied by headaches due to hypertension. The diagnosis of sleep pattern disturbance was confirmed based on subjective and objective data. The intervention involved the administration of lavender aromatherapy, hypertension management, and creating a comfortable sleep environment. The intervention was implemented consistently over three days, resulting in significant improvements in the patient’s sleep patterns. The evaluation indicated that Mrs. T experienced better sleep quality, slept more soundly, and showed stable blood pressure. The conclusion of this study is that lavender aromatherapy is effective in addressing sleep pattern disturbances in elderly patients with hypertension, contributing to reduced blood pressure and alleviated headaches. Lavender aromatherapy can be considered a safe and easily applicable non pharmacological intervention for elderly patients with sleep disturbances.Keywords: Sleep pattern disturbances, Lavender aromatherapy, Elderly with hypertension